2017
DOI: 10.1002/smr.1896
|View full text |Cite
|
Sign up to set email alerts
|

The connections between group maturity, software development velocity, and planning effectiveness

Abstract: Empirical evidence regarding the connection between group development (maturity) and the success of software development teams is lacking. The purpose of this research is to gain a qualitative and quantitative understanding of how velocity and planning effectiveness of software teams connect to a group development model. The Group Development Questionnaire was given to 19 software developers from 4 work groups to assess their group development maturity. The work groups' responses to the survey were checked for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Al‐Sabbagh and Gren found that the fourth stage of group development was strongly correlated with planning effectiveness, and they did not find any important correlation between group maturity and velocity. The correlations between aspects of group maturity and the effort to develop UCPs were not found to be statistically significant in the present work; however, some correlations between team efficiency and aspects of group maturity were found to be strong and statistically significant.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Al‐Sabbagh and Gren found that the fourth stage of group development was strongly correlated with planning effectiveness, and they did not find any important correlation between group maturity and velocity. The correlations between aspects of group maturity and the effort to develop UCPs were not found to be statistically significant in the present work; however, some correlations between team efficiency and aspects of group maturity were found to be strong and statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…Al‐Sabbagh and Gren suggested that, to increase the performance of software teams, groups must clarify roles and communicate process‐related issues. Strong correlations between efficiency and clarity of roles and goals, and between communication and effectiveness, were found in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…responsiveness to requests for information, prior relationship history, etc. ), technical and group proficiency of the team members, and the capabilities of the technologies used [16]. The team is extremely conscious of any delays in the project timeline as delays in project delivery have a career, pay and reputational implications for the developers concerned.…”
Section: Assurance Review and Control (Arc) Effortmentioning
confidence: 99%
“…Therefore, this paper looks closer into the planning effectiveness of social groups within software development due to effectiveness being more tangible than group performance. We measure team effectiveness in this study as estimated effort divided by spent effort, just like in Al-Sabbagh and Gren [15].…”
Section: Introductionmentioning
confidence: 99%